(untitled) (Itinera, 2015)
The present essay aims at showing how the continuous improvement of biotechnology and nanotechnology causes an artificial redesign of human nature. This artificial redesign implies the idea of homo cyborg, the concept of which, as developed by some post-human movements, sees man as future maker of himself. The distinguishing features of homo cyborg are the autonomy of rationality and the rejection of physical limitations. The present essay is articulated in the following three parts: 1) analysis of the main points of view which mark the contemporary rationalistic and systematic hermeneutics of man and his behaviors; 2) illustration of the impossibility for this hermeneutics to adhere to the essence of life, the peculiarity of which exceeds the interpretative prerogative of man; 3) explanation of the concepts of “indeterminateness” and “crossroad” as keywords of human nature, that preserve creativity and improvisation as fundamental pedagogical means of improvement of human ability.